Perovskite Quantum Dots with Near Unity Solution and Neat‐Film Photoluminescent Quantum Yield by Novel Spray Synthesis. Issue 7 (22nd December 2017) - Dai, Shu‐Wen; Hsu, Bo‐Wei; Chen, Chien‐Yu; Lee, Chia‐An; Liu, Hsiao‐Yun; Wang, Hsiao‐Fang; Huang, Yu‐Ching; Wu, Tien‐Lin; Manikandan, Arumugam; Ho, Rong‐Ming; Tsao, Cheng‐Si; Cheng, Chien‐Hong; et al.
Abstract: In this study, a novel perovskite quantum dot (QD) spray‐synthesis method is developed by combining traditional perovskite QD synthesis with the technique of spray pyrolysis. By utilizing this new technique, the synthesis of cubic‐shaped perovskite QDs with a homogeneous size of 14 nm is demonstrated, which shows an unprecedented stable absolute photoluminescence quantum yield ≈100% in the solution and even in the solid‐state neat film. The highly emissive thin films are integrated with light emission devices (LEDs) and organic light emission displays (OLEDs). The color conversion type QD‐LED (ccQD‐LED) hybrid devices exhibit an extremely saturated green emission, excellent external quantum efficiency of 28.1%, power efficiency of 121 lm W −1, and extraordinary forward‐direction luminescence of 8 500 000 cd m −2 . The conceptual ccQD‐OLED hybrid display also successfully demonstrates high‐definition still images and moving pictures with a 119% National Television System Committee 1931 color gamut and 123% Digital Cinema Initiatives‐P3 color gamut. These very‐stable, ultra‐bright perovskite QDs have the properties necessary for a variety of useful applications in optoelectronics. Abstract : Spray‐synthesized perovskite quantum dots (QDs) show an unprecedented cubic shape, and a stable photoluminescence quantum yield of ≈100% in both solution and the solid‐state neat film. QD‐LED (light emission device) and QD‐OLED (organic light emission display) hybrid devices exhibit an excellent external quantum efficiency of 28.1%, a power efficiency of 121 lm W −1, and successfully demonstrate high‐definition motion pictures.